Nano-hydroxyapatite-incorporated polycaprolactone nanofibrous scaffold as a dentin tissue engineering-based strategy for vital pulp therapy - Mendes Soares, Igor Paulino [UNESP]; Anselmi, Caroline [UNESP]; Kitagawa, Fernanda Ali [UNESP]; Ribeiro, Rafael Antonio de Oliveira [UNESP]; Leite, Maria Luísa; de Souza Costa, Carlos Alberto [UNESP]; Hebling, Josimeri [UNESP] (Elsevier, 2022)
Objectives: Targeting a tissue engineering-based vital pulp therapy (VPT), this study investigated the incorporation of nano-hydroxyapatite (nHA) into polycaprolactone (PCL) nanofibers, and the metabolism of human dental pulp cells (HDPCs) seeded on the scaffolds. Methods: PCL-based solutions (10% w/v) containing nHA (0 – control; 0.5; 1.0; or 2.0% w/v) were electrospun into nanofibrous scaffolds. The scaffolds were characterized for morphology and composition (MEV/EDS), solubility, the release of calcium/phosphate (C/P), and modulation of medium pH. Then, HDPCs were seeded on the scaffolds and evaluated for cell viability (alamarBlue and live/dead), adhesion and spreading (F-actin), total protein (TP; Lowry), alkaline phosphatase activity (ALP; thymolphthalein assay), expression of odontogenic genes (RT-qPCR), and formation of a mineralized matrix (Alizarin Red). Data were analyzed with ANOVA and post-hocs (α = 5%). Results: Higher nHA concentrations roughened fiber surfaces, whereas PCL+ 2%nHA increased the interfibrillar spaces. PCL+ 1%nHA or PCL+ 2%nHA significantly released more C/P but the medium pH was maintained below 8.0. HDPCs viability was not affected by nHA, while cell adhesion/spreading was favored, especially for PCL+ 2%nHA. Higher protein content and ALP activity were seen for scaffolds incorporated with nHA, after 21 days. PCL+ 1%nHA and PCL+ 2%nHA upregulated the expression of DSPP and DMP1 in 14 days, and COL1A1, ALPL, and DMP1 in 21 days. The formation of a mineralized matrix was nHA concentration-dependent, and it was about 9 × higher for PCL+ 2%nHA. Significance: nHA-incorporated PCL nanofibrous scaffolds are cytocompatible and can stimulate the adhesion and odontogenic potential of HDPCs. PCL+ 2%nHA formulation is a bioactive tissue engineering-based cell-homing strategy for VPT.
Keywords: Calcium-phosphate ceramics; Cell-homing therapy; Hydroxyapatites; Nanofiber; Pulp capping agents; Scaffold; Tissue engineering